Pendidikan, Pekerjaan Orangtua dan Tingkat Kebersihan Gigi dan Mulut Anak dengan Down syndrome - Siti Fitria Ulfah; Agus Marjianto (FORIKES, 2023)
Children with Down syndrome cannot perform dental and oral hygiene independently due to cognitive and motoric limitations, even though this is important for optimal dental and oral health conditions. The purpose of this study was to analyze the relationship between educational level and parental occupation with the level of dental and oral hygiene of people with Down syndrome in the Surabaya area. The research design was cross-sectional. The sample size was 100 respondents consisting of parents and children with Down syndrome who were selected by simple random sampling technique. Primary data collection was carried out by filling out a questionnaire to find out the level of education and occupation of parents; while a clinical examination of the oral cavity was carried out to measure the level of dental and oral hygiene using OHIS measurements. Analysis of the relationship test between variables was carried out with the Chi-square test. The results showed that the p-value was 0.306 for the correlation analysis between parents' education level and oral hygiene level, and 0.208 for the correlation analysis between parents' occupation and oral hygiene level. It was concluded that the level of dental and oral hygiene of children with Down syndrome in the Surabaya area was not related to the level of education and occupation of their parents.Keywords: dental and oral hygiene; down syndrome; parent; education; work; parent ABSTRAK Anak dengan down syndrome tidak bisa melakukan kebersihan gigi dan mulut secara mandiri karena adanya keterbatasan kognitif dan motorik, padahal ini penting untuk mendapatkan kondisi kesehatan gigi dan mulut yang optimal. Tujuan penelitian ini adalah menganalisis hubungan antara tingkat pendidikan dan pekerjaan orangtua dengan tingkat kebersihan gigi dan mulut penderita down syndrome di wilayah Surabaya. Rancangan penelitian ini adalah cross-sectional. Ukuran sampel adalah 100 responden yang terdiri dari orangtua dan anak dengan down syndrome yang dipilih dengan teknik simple random sampling. Pengumpulan data primer dilakukan dengan pengisian kuesioner untuk mengetahui tingkat pendidikan dan pekerjaan orangtua; sedangkan pemeriksaan klinis rongga mulut dilakukan untuk mengukur tingkat kebersihan gigi dan mulut menggunakan pengukuran OHIS. Analisis uji hubungan antara variabel dilakukan dengan uji Chi-square. Hasil penelitian menunjukkan nilai p adalah 0,306 untuk analisis korelasi antara tingkat pendidikan orang tua dengan tingkat kebersihan gigi dan mulut, serta 0,208 untuk analisis korelasi antara pekerjaan orangtua dengan tingkat kebersihan gigi dan mulut. Disimpulkan bahwa tingkat kebersihan gigi dan mulut anak dengan down syndrome di wilayah Surabaya tak berhubungan dengan tingkat pendidikan dan pekerjaan orangtua.Kata kunci: kebersihan gigi dan mulut; down syndrome; orang tua; pendidikan; pekerjaan; orangtua